Some combinatorial algorithms connecting hypergraphs - Thi, Vũ Đức (Journal of Computer Science and Cybernetics, 2016)
In the relational datamodel the combinatorial algorithms are constructed many authors. The hypergraph is a important concept in the combinatorial theory. The candidate keys play an essential role in the relational datamodel. In this paper, base on hypergraph we present a new combinatorial algorithm that finds all candidate keys of a give relation. Some another results related to the candidate keys are given.